Combined surgical and endovascular treatment of complex cerebrovascular diseases in the hybrid operating room. (2nd June 2012) - Murayama, Yuichi; Arakawa, Hideki; Ishibashi, Toshihiro; Kawamura, Daichi; Ebara, Masaki; Irie, Koreaki; Takao, Hiroyuki; Ikeuchi, Satoshi; Ogawa, Takeki; Kato, Masataka; Kajiwara, Ikki; Nishimura, Shingo; et al.
Abstract : Background: Although most neurovascular diseases can be treated either by microsurgical or endovascular means, a subset of patients may require a combined approach. Patient transfer from the operating room (OR) to the angiosuite has been a fundamental drawback of this type of approach. Objective: The purpose of this study is to report our clinical experience performing combined surgical and endovascular procedures for neurovascular diseases in the hybrid OR. Methods: 29 patients with neurovascular diseases underwent combined endovascular and surgical procedures in a single session: 16 were scheduled combined treatment and 13 were emergency combined procedures. Of the emergency cases, three were rescue surgeries after endovascular complications. Three patients had ruptured intracranial aneurysms, eight had unruptured intracranial aneurysms, eight had arteriovenous malformations and eight had arteriovenous fistulae; two patients had either a spinal tumor or dural arteriovenous fistulae. Results: All combined procedures were performed in a single session without changing the patient's surgical position. In cases of ruptured arteriovenous malformations or aneurysms with hematoma, an emergency embolization was performed to assist the surgical procedure. Combined superficial temporal artery–middle cerebral artery (STA–MCA) bypass followed by endovascular parent artery trapping were successfully performed for complex large or giant aneurysms. There were two periprocedural ischemic complications. Of the three patients who underwent surgical rescue after endovascular complications, two remained intact and one died despite immediate surgical procedures. Conclusion: A combined endovascular and surgical approach conducted in a hybrid OR provides a new strategy for the treatment of complex neurovascular diseases.